2001
DOI: 10.1046/j.1365-2389.2001.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of heteronuclear and multidimensional NMR spectroscopy of humic substances

Abstract: Summary Mapping the chemical structures and organization of humic substances is vital for a fundamental understanding of their roles and interactions in the soil. One‐dimensional nuclear magnetic resonance (NMR) techniques have advanced our awareness of the composition of humic materials, but modern developments in two‐dimensional NMR are soon likely to make obsolete reliance on one‐dimensional spectra alone. The advantages of using heteronuclear two‐dimensional NMR spectroscopy are illustrated in this paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 21 publications
5
70
0
1
Order By: Relevance
“…Canellas et al (2008b) studied the exudation profile of plants treated with humic substances and observed that the presence of citric acid, as well as malic, tartaric, and oxalic acids, increased in exudates of corn roots. Chromatographic analysis of these solutions revealed the presence of low-molecular-weight substances only, indicating the separation of the humic acids aggregate that was initially applied and corroborating previous results obtained by Piccolo et al (1996a, b), Piccolo (2001) and Simpson (2001). These findings confirm the biomolecules' provider property conceptualized by Sposito (2008) for humic acids, and also as biostimulants, which was as well observed by Nardi et al (2002), Canellas et al (2002Canellas et al ( , 2008a Zandonadi (2006) and Zandonadi et al (2007) and Canellas et al (2008a).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Canellas et al (2008b) studied the exudation profile of plants treated with humic substances and observed that the presence of citric acid, as well as malic, tartaric, and oxalic acids, increased in exudates of corn roots. Chromatographic analysis of these solutions revealed the presence of low-molecular-weight substances only, indicating the separation of the humic acids aggregate that was initially applied and corroborating previous results obtained by Piccolo et al (1996a, b), Piccolo (2001) and Simpson (2001). These findings confirm the biomolecules' provider property conceptualized by Sposito (2008) for humic acids, and also as biostimulants, which was as well observed by Nardi et al (2002), Canellas et al (2002Canellas et al ( , 2008a Zandonadi (2006) and Zandonadi et al (2007) and Canellas et al (2008a).…”
Section: Introductionsupporting
confidence: 89%
“…When, operationally, ionization is promoted using alkali extractants, both groups are dissolved, whereas acidification provides precipitation of the so-called humic acids only, which are less polar than fulvic acids. Additionally, acidification of humic acids solution with citric acid may influence the structure and conformation of the supramolecular arrangement of these humic substances, with a relative disintegration of these clusters, increasing their reactivity (Piccolo et al 1996a, b;Piccolo, 2001;Simpson, 2001). Sposito (2008) emphasizes that humic substances, designated as supramolecules by Piccolo (2001), would have the properties of biomolecules from which they are derived: fragments that form an integral or labile part of the molecular architecture and thus control their conformation, chemical reactivity and bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasis that this report presents only those highlights of a 5-year effort necessary to substantiate our concepts and conclusions. Detailed considerations of the applications and interpretations of the various NMR experiments are beyond the scope of this communication and are discussed in detail by Simpson et al (1997bSimpson et al ( , 2001a, Kingery et al (2000), and Simpson (2001).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, improvements in NMR hardware, stability, and sensitivity have kept pace in both solid -state and solution -state NMR. Thus, it is not surprising that in the last decade the application of multidimensional NMR has grown exponentially (Simpson et al, 1997(Simpson et al, , 2001a(Simpson et al, ,c, 2002a(Simpson et al, , 2003aHaiber et al, 1999Haiber et al, , 2001aFan et al, 2000 ;Kingery et al, 2000 ;Knicker, 2000a ;Simpson, 2001 ;Hertkorn et al, 2002bHertkorn et al, , 2006Cook et al, 2003 ;Kaiser et al, 2003 ;Kim et al, 2003 ;Cardoza et al, 2004 ;Mao and Schmidt -Rohr, 2006 ). In 1989, the fi rst applications of multidimensional NMR were applied to humic substances (Buddrus et al, 1989 ).…”
Section: Structural Studies Of Nommentioning
confidence: 99%
“…In 2000, studies showed that humic acid had a considerable peptide content (Fan et al, 2000 ), and that 2D NMR was applicable to the study of the IHSS standard soil humic acid (Kingery et al, 2000 ). In the following year, Simpson et al applied a full suite of NMR experiments, including COSY, TOCSY, HSQC, HMQC -TOCSY, HMBC, and NOESY, to the study of a charge -fractionated fulvic acid and attempted detailed interpretation of the data (Simpson et al, 2001a ). Furthermore, the same group offering a practical guide and review (Simpson, 2001 ) demonstrated the applicability of HR -MAS NMR (Simpson et al, 2001b ) and the application of DOSY to separate NOM components (Simpson et al, 2001c ).…”
Section: Structural Studies Of Nommentioning
confidence: 99%